Stem cell senescence drives age-attenuated induction of pituitary tumours in mouse models of paediatric craniopharyngioma. Issue 1 (December 2017) - Gonzalez-Meljem, Jose Mario; Haston, Scott; Carreno, Gabriela; Apps, John R.; Pozzi, Sara; Stache, Christina; Kaushal, Grace; Virasami, Alex; Panousopoulos, Leonidas; Mousavy-Gharavy, Seyedeh Neda; Guerrero, Ana; Rashid, Mamunur; et al.
Abstract Senescent cells may promote tumour progression through the activation of a senescence-associated secretory phenotype (SASP), whether these cells are capable of initiating tumourigenesis in vivo is not known. Expression of oncogenic β-catenin in Sox2+ young adult pituitary stem cells leads to formation of clusters of stem cells and induction of tumours resembling human adamantinomatous craniopharyngioma (ACP), derived from Sox2− cells in a paracrine manner. Here, we uncover the mechanisms underlying this paracrine tumourigenesis. We show that expression of oncogenic β-catenin in Hesx1+ embryonic precursors also results in stem cell clusters and paracrine tumours. We reveal that human and mouse clusters are analogous and share a common signature of senescence and SASP. Finally, we show that mice with reduced senescence and SASP responses exhibit decreased tumour-inducing potential. Together, we provide evidence that senescence and a stem cell-associated SASP drive cell transformation and tumour initiation in vivo in an age-dependent fashion. Senescent cells can promote tumour progression through the activation of a senescenceassociated secretory phenotype (SASP). Here, the authors show that SASP activation is associated with non-cell autonomous cell transformation and tumour initiation in an in vivo model of adamantinomatous craniopharyngioma.